Personal financing product of KFHMB: a case study on Murabahah Tawarruq Concept / Siti Saidatul Nadia Saadon - Saadon, Siti Saidatul Nadia (2009)
Islamic finance and Banking is no longer just a theory or a dream. In fact it is now a reality, most of the Islamic banks and financial institutions mostly Muslim community and non Muslims are using Murabahah as an Islamic mode of financing, and most of their financing operations are based on Murabahah. That is why this term has been taken in the economic circles today as a method of banking operations, while the original concept of Murabahah is different from this assumption. Murabahah is, in fact, a term of Islamic Fiqh and it refers to a particular kind of sale having nothing to do with financing in its original sense. This concept refers to the sale of goods at a price, which includes a profit margin to by both parts. The basic element that makes Murabahah different from the other Islamic fiqh terms Murabahah that the seller discloses the actual cost he has incurred in acquiring the commodity, and then adds some profit thereon in other words disclosing the actual information. Futhermore, in principle, Murabahah financing is suitable for situations where the customer requires funds for the purchase of identifiable assets. However, businesses often need cash financing to fund expenditure not attributable to identifiable assets such as pay wages and salaries. Therefore in this research, reseacher try to observe concept of Murabahah and Tawarruq in term of financing and examine whether combination of Murabahah Tawarruq performs effectively compared to Murabahah as applied by KFHMB personal financing.